Characteristics and outcomes of transjugular intrahepatic portosystemic shunt recipients in the VA Healthcare System. Issue 6 (June 2016) - Lerrigo, Robert; Beste, Lauren A.; Leipertz, Steven L.; Green, Pamela K.; Lok, Anna S.F.; Kogut, Matthew J.; Ioannou, George N.
Abstract : Background and Aims: Transjugular intrahepatic portosystemic shunt (TIPS) placement is an effective treatment for complications of portal hypertension. We aimed to describe post-TIPS mortality and its predictors in the modern era of covered stents. Patients and methods: We identified patients with cirrhosis who underwent TIPS insertion at Veterans Affairs Healthcare facilities nationally from 2004 to 2014 ( n =703), most of which (95%) were performed as elective procedures. We followed patients until the date of death, transplantation, or the end of the observation period. Results: TIPS recipients had a mean age of 59.3 years (SD 8) and 97% were men. The mean Model for End Stage Liver Disease (MELD) score was 13 (SD 4.8); 47% had hepatitis C virus (HCV) infection, 48% had variceal hemorrhage, and 40% had ascites. During a mean follow-up of 1.72 years (SD 1.9), 57.5% of TIPS recipients died ( n =404) and only 5.3% underwent liver transplantation ( n =37). The median survival after TIPS was 1.74 years (interquartile range 0.3–4.7). Thirty-day mortality after TIPS was 11.6% [95% confidence interval (CI) 9.4–14.2], 1-year mortality was 40.3% (95% CI 36.7–44.2), and 3-year mortality was 61.9% (95% CI 57.9–66.0). Independent predictors of post-TIPS mortality included medical comorbidity burden, low albumin, HCV infection, and high MELD score (or high international normalized ratio and bilirubin when the components of the MELD score were analyzed individually). TIPS revision was performed at least once in 27.3% of TIPS recipients. Conclusion: TIPS should not be considered simply as a bridge to transplantation. Burden of extra-hepatic comorbidities, HCV infection, and low serum albumin strongly predict post-TIPS mortality in addition to the MELD score. Abstract : Supplemental Digital Content is available in the text.